A Procedure for the Characterization of Monocapillary X-Ray Lenses as Condensers for Full-Field Transmission X-Ray Microscopes - Sun, Xuepeng; Shao, Shangkun; Li, Huiquan; Zhang, Xiaoyun; Yuan, Tianyu; Tao, Fen; Sun, Tianxi (Frontiers in Physics, 2022)
Monocapillary x-ray lenses (MXRLs) are mostly used as condensers in full-field transmission x-ray microscopy (TXM) based on synchrotron radiation or laboratory x-ray tubes. The performance of the condenser has a significant impact on the imaging quality of the TXM. In this paper, a procedure for the characterization of the MXRL as a condenser is presented. The procedure mainly includes two parts: optical measurement and x-ray tests. From the test results of the characterization procedure, it can be seen that a relatively high-performance condenser can be screened out from a series of MXRLs drawn by an electric furnace. This is also fed back to the manufacturing process, and therefore, the technology of manufacturing the condenser can be gradually optimized. Moreover, the method of characterizing the performance of the condenser designed for synchrotron radiation TXM by laboratory x-ray tubes is proposed to be used in this procedure, which effectively reduces the manufacturing time of high-performance condensers for synchrotron radiation TXM.